Hormone-Mediated Strategies to Enhance Training and Performance - Beaven, Christopher Martyn (Auckland University of Technology, 2010)
Rugby union is a highly competitive and physically demanding contact sport in which successful outcomes rely, inherently, on strength, power, speed, and endurance. Resistance training is a potent stimulus for skeletal muscle strength and power adaptation, and training stimuli and loads modulate adaptation. Adaptive responses are mediated by cellular and molecular events, and actualised by alterations in gene expression. The steroid hormones testosterone and cortisol play a role in the adaptive process and subsequent training outcomes. This thesis investigates strategies intended to modify salivary hormone responses and affect resistance training outcomes. A literature review examined the cellular response of skeletal muscle tissue to resistance exercise with attention focussed on how testosterone and cortisol mediate adaptive outcomes. The acute testosterone and cortisol responses to complex training were investigated in Chapter Three. Sixteen rugby players performed four exercise protocols in a cross-over manner: power-power; power-strength; strength-power; or strength-strength. The most noteworthy responses were a small testosterone elevation and a trivial elevation in cortisol following the strength-power protocol, suggesting that this exercise sequence elicited an enhanced anabolic state compared to the other exercise protocols. An interaction between hormonal circadian rhythms and exercise stimulus was investigated in Chapter Four. Eight rugby players performed identical squat training over four weeks either in the morning or in the afternoon. Clear differences were observed between pre- and post-exercise hormone concentrations, and the ratio of testosterone to cortisol was elevated in the afternoon. Training resulted in similar increases in box squat strength regardless of time performed; however peak power increased to a greater extent when training was performed in the afternoon. This observation suggested that circadian rhythmicity has the potential to modulate specific adaptations to resistance exercise. The effect of the ultradian pulsatility of testosterone and cortisol, and their interaction with the hormonal responses to physiological and psychological stimuli, were investigated in Chapter Five. Testosterone and cortisol concentrations of seven males were measured every 10 min between 0800 and 1600 h on three consecutive days. Analysis was consistent with episodic testosterone pulses on non-intervention days. A sprint intervention elicited a small elevation in testosterone and this response correlated with the change in testosterone concentration in the 10 min prior to exercise. Thus, the testosterone response to exercise may be related to the ultradian biorhythm. This interaction could have important implications for adaptation to exercise. The ability of caffeine to modify the hormonal response to exercise was investigated in Chapter Six. A double-blinded, placebo controlled study with 24 athletes ingesting 0, 200, 400, or 800 mg doses of caffeine, assessed testosterone and cortisol responses to resistance exercise sessions. Exercise elevated testosterone, and caffeine enhanced this response in a dose-dependent manner. However, caffeine also produced an elevation in cortisol, and thus the anabolic effects of the testosterone increase may be counteracted by the catabolic effects of cortisol. In conclusion, it has been demonstrated that various strategies are capable of modulating the testosterone and cortisol response to exercise stimuli, and thus have implications for subsequent adaptation and performance.
Keywords: Testosterone; Cortisol; Rugby